Think about and intervene in the territory through the Actor Network Theory Pensar e intervenir el territorio a traves de la Teoria del Actor-Red - Juan E. Cabrera (Athenea Digital, 2011)
The purpose of this article is to think about the similarities between the ways of seeing the territory as a network, some theoretical positions about the territory concept and actor network theory. After focusing on proposing a way of understanding the relationships between actors when they will intervene in the territory through the public policies and territorial planning, i ll try to apply the ANT model of public policy management through the guidance of ANT El propósito de este artículo es reflexionar sobre las coincidencias entre la forma de ver el territorio como red, algunas posturas teóricas sobre su concepto y la teoría del actor-red. Sobre lo anterior se centra en proponer una forma de entender las relaciones entre actores cuando se va a intervenir el territorio a través de políticas públicas como la planificación utilizando un modelo de gestión territorial a través de las orientaciones de la TAR.